Online Conversation Analysis as The Research Method of Social Media Texts: Rationale, Steps and Example - Aurelius R.L. Teluma (Universitas Mataram, 2019)
The main components of social media text are the language and network structure of users. Virtually, social media texts appear in the form of posts and comments. Therefore, social media texts have the characteristics of online conversation. So, online conversation analysis (OCA) is one of the important research methodologies for reviewing social media texts. This paper aims to provide a rationale, steps, and examples of online conversation analysis practices. The most important aspect of the conversation is conversational coherence, namely the connection and meaningfulness in conversation. However, asynchronous factors, information abundance and identity problems in social media texts make such analysis require a number of additional steps. The steps for analyzing online conversations include these aspects: turn taking structures, construction of exchanges, parts-alliances-talks, trouble and repair, preferences and accountability, institutional category and identity. Keywords: online conversation analysis; social media text; research method